Mluvím, a tedy jsem // I Speak, Therefore I Am - Marie Langerová (Slovo a Smysl, 2016)
In 1960s Czechoslovakia, experimental poetry became an important part of the conceptual turnaround in art. The language in this poetry had its own weight as an object, which, however, lost its function and participated the programs of its own self-destruction. The language of poetry interceded in various fields — the creation of art, new music, sciences. From the end of the 1950s, the poems (‘written by voice’) of Ladislav Novák arose analogously to visual poetry. These unique magnetic tape records were, in the course of the 1960s, put into the international context of vocal poets — Henri Chopin, Ilse and Pierre Garnier, Bernard Heidsieck, Franz Mon, Gerhard Rühm, and so on. This phonetic poetry became part of the search for a universal language of experimental poetry, yet, at the same time opened a new conception of the relationship between poetry and music.